Mangrove restoration in Vietnamese Mekong Delta during 2015-2020: Achievements and challenges - Tinh, Pham Hong; MacKenzie, Richard A.; Hung, Tran Dang; Vinh, Truong Van; Ha, Hoang Thi; Lam, Mai Huong; Hanh, Nguyen Thi Hong; Tung, Nguyen Xuan; Hai, Pham Minh; Huyen, Bui Thanh (Frontiers in Marine Science, 2022)
Mangrove forest in the Mekong Delta plays important roles in protecting coasts from soil erosion and strong waves, supplying seafood, and accumulating carbon. Despite these benefits, mangroves have been and continue to be severely damaged by the impacts of natural and socioeconomic activities. In recent years, large areas of mangrove forest have been restored through planting and other various management actions. In this study, we analyzed high-resolution WorldView-2 images to quantify changes in the mangrove forest in seven coastal provinces (Tien Giang, Ben Tre, Tra Vinh, Soc Trang, Bac Lieu, Ca Mau, and Kien Giang) of the Mekong Delta from 2015 to 2020. Our study is one of the first to analyze mangrove forest change at the commune scale, the smallest official administrative unit in Vietnam, to determine the area of restored mangroves. The potentials and challenges in future mangrove restoration were also assessed by analyzing satellite imagery and field survey data. In the study area, mangrove forest area increased by 11,184 ha (approximately 2,237 ha per year) from 79,593 ha in 2015 to 90,777 ha in 2020. A total area of 16,138 ha (approximately 20.3%) was lost due to mangrove conversion to other land uses, aquaculture activities and coastal erosion, etc., while 27,322 ha (approximately 34.1%) was restored or newly planted during state- and NGO-funded mangrove restoration projects and programs. These results confirmed that mangrove restoration projects and programs have played a significant role in maintaining and increasing mangrove forest cover in Mekong Delta. The results can also assist managers and decision makers in mangrove restoration evaluation, and suggest analyzing WorldView-2 images to monitor mangrove restoration over time in Vietnam.